2007
DOI: 10.3354/meps07192
|View full text |Cite
|
Sign up to set email alerts
|

Bait attraction affects the performance of remote underwater video stations in assessment of demersal fish community structure

Abstract: Discriminating marine fish assemblages at broad scales can be difficult because of heterogeneity within their habitats, variability in patterns of behaviour and abundance of fish between habitats, and sampling biases in extractive fishing techniques when used across a range of habitats. Remote underwater video stations have recently been developed to help overcome these problems, but the use of bait as an attractant raises questions about bias towards scavengers and predators in samples of fish communities. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
264
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(285 citation statements)
references
References 29 publications
9
264
2
Order By: Relevance
“…The method for sampling fi sh populations with a baited stereo-video camera system has been found to generate more consistent data than have comparable unbaited systems (Harvey et al, 2007), has the ability to detect mobile fi sh species (Harvey et al, 2007;Watson et al, 2010), and has been determined to be effective in sampling bottomfi shes in Hawaii (Ellis and DeMartini, 1995;Merritt et al, 2011). The BotCam is a means by which bottomfi sh abundance estimates can be made within actual bottomfi sh habitats and fi sh lengths can be accurately measured.…”
Section: Methodsmentioning
confidence: 99%
“…The method for sampling fi sh populations with a baited stereo-video camera system has been found to generate more consistent data than have comparable unbaited systems (Harvey et al, 2007), has the ability to detect mobile fi sh species (Harvey et al, 2007;Watson et al, 2010), and has been determined to be effective in sampling bottomfi shes in Hawaii (Ellis and DeMartini, 1995;Merritt et al, 2011). The BotCam is a means by which bottomfi sh abundance estimates can be made within actual bottomfi sh habitats and fi sh lengths can be accurately measured.…”
Section: Methodsmentioning
confidence: 99%
“…To reduce biases and limiting parameters, scientists have increasingly resorted to using video survey systems, such as baited (or unbaited) remote underwater video (BRUV) during the day or night (Francour et al 1999, Denny et al 2004, Harvey et al 2007, Colton & Swearer 2010. These video methods are used to avoid some biases due to UVC (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Sampling Biases: What Are We Missing?-Technical advances including remote underwater video, baited video, stereo-video, diving equipment, and sonic telemetry have catalyzed a previously unimaginable breadth of marine research (Willis et al 2000, Harvey et al 2007, Davis et al 2015, Sopinka 2015, Lindfield et al 2016. In the present study, we found diel activity data for 835 species of epipelagic fish from 68 studies (Online Appendix 1), reflecting the continual advancement of tools that enable underwater research.…”
Section: Discussionmentioning
confidence: 66%